Tenaga Kerja pada Proses Produksi Bak Dump Truck di Karoseri PT. Ragam Mulya Abadi - Kurnia, Alfadhil Surya; Sajiyo, Sajiyo; Yuwono, Istantyo (Fakultas Teknik UMRI, 2024)
PT. Ragam Mulya Abadi, a commercial vehicle construction company, is located at Jalan Raya Menganti Jeruk No 296a, Lakarsantri, Surabaya, East Java, Indonesia. The company operates from 08:00 to 17:00, with work being conducted for 9 hours per day. Currently, the company does not have a network diagram or understanding of the critical path in its projects. A network diagram illustrates the production process and relationships between activities in the project, while the critical path is a series of crucial steps that must be completed on time to ensure production stays on schedule. Standard time studies use the stopwatch time study method to improve production efficiency, identify critical paths, and understand fluctuations in labor requirements over the course of a year. With a total standard time of 190 minutes and the critical path A-B-D-E-G-H requiring 3.9 hours, the company can plan and execute projects more efficiently.Keywords: network diagram, standart time, production, efficient, stopwatch time study.